1997
DOI: 10.14219/jada.archive.1997.0257
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Range of Surgical Effects on Soft Tissue Produced by a Carbon Dioxide Laser

Abstract: The authors investigated the surgical and collateral effects on soft tissue of a carbon dioxide laser emitting at 9.3 micrometers. Specifically, incision widths and depths as well as effectiveness were studied. Three different laser modes were investigated: gated continuous wave, or Cw, Superpulse and OptiPulse (Medical Optics). Incision depths correlated positively with average power; higher powers produced deeper incisions. The gated Cw mode quickly produced wide, deep incisions; Superpulse achieved narrower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 11 publications
2
29
4
Order By: Relevance
“…23,24 When a CO 2 laser is used for soft tissue surgeries, the conversion of energy into heat produces a lateral thermal damage zone, where no evaluation of the cell morphology is possible because of the denatured tissue. 4,[16][17][18] The simulation of cytologic atypias in the deeper tissue layers also has been described. [25][26][27] The thermally denatured tissue also represents a barrier to healing of the wound site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 When a CO 2 laser is used for soft tissue surgeries, the conversion of energy into heat produces a lateral thermal damage zone, where no evaluation of the cell morphology is possible because of the denatured tissue. 4,[16][17][18] The simulation of cytologic atypias in the deeper tissue layers also has been described. [25][26][27] The thermally denatured tissue also represents a barrier to healing of the wound site.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,[12][13][14] The CO 2 laser can be used in different modes, ranging from continuous wave to pulsed modes in the range of microseconds emitted with a defined frequency. 15,16 Histopathologically, different thermal damage zones have been described with different laser modes. [16][17][18] It has been speculated that delayed wound healing may be due to the extent of the lateral thermal damage zone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Laser transmitted through optical fibres needs only a very small space (200-600 mm) and can remove diseased tissue with great precision compared with conventional treatment. In the past, mainly CO 2 -, Ho:YAGand Nd:YAG lasers have been investigated for medical applications (Whipple et al, 1987;Romanos, 1994;Wilder-Smith et al, 1997;Sherk et al, 2002). However, thermal damage to the irradiated tissue and the surroundings remains a great concern (White et al, 1991, Absten, 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Lasers parameters such as power, repetition rate, average power and highest peak power play a role in surgical and collateral effects. Studies have concluded that high repetition rate, high peak power and lower average power yield favourable clinical results (Wilder-Smith, Dang, & Kurosaki, 1997 Due to the lack of tactile sensation, their use in hard-tissue applications is not favorable.…”
Section: Basic Equipment Design and Tissue Interactions Of Co2 Lasermentioning
confidence: 99%